Obtaining protein preparations of the first subunit of hemagglutinin influenza virus (Experimental biology, 2020)
At the moment, there is considerable concern about the spread in the world of epizootics of the highly pathogenic avian influenza virus. Influenza virus has the highest genetic variability and the likelihood of new strains that can create large epidemics. The evolution of the influenza virus proceeds very quickly, therefore, the paramount task of the researchers is antigenic mapping of hemagglutinin subtypes, as well as identifying the characteristics of the antigenic structure. X-ray crystallography is a commonly used method for determining the three-dimensional structure of a protein.The purpose of these studies was to obtain a recombinant protein of the first hemagglutinin subunit by bacterial expression in Escherichia coli to further determine its three-dimensional structure.As a result of the research, a plasmid containing the nucleotide sequence of a gene encoding the target protein of the first hemagglutinin subunit was transformed into E. coli cells, strain ER2566. The optimal conditions for the expression of the target gene in E. coli cells, strain ER2566, and purification of the recombinant protein by metal affinity chromatography were worked out. The degree of protein purification was at least 95%. The resulting recombinant protein will be used for further work on crystallography and three-dimensional modeling of the protein. Key words: avian influenza virus, hemagglutinin, expression, recombinant protein.